LINGUISTIC REFLECTION OF LEXICOGRAPHIC EUPHEMIZATION IN THE COMPARATIVE-CONTRASTIVE ASPECT OF RUSSIAN AND UZBEK CULTURES - Sattarova Elena Anatolyevna (Bright Mind Publishing, 2025)
This article presents a comparative analysis of lexicographic euphemization in Russian and Uzbek cultures. In studying Russian and Uzbek dictionaries, we discovered that the recording and implementation of euphemistic space at the lexicographic level barely reflects the use of borrowed words and terms at the linguistic and lexical levels. Therefore, the analysis of the collected material was based on the principle of interpretation. It should be noted that the meanings of euphemisms represent complex material for lexicography. Nevertheless, an in-depth study will allow us to draw conclusions about the resources that contribute to the formation of euphemistic results and are reflected in modern explanatory dictionaries, as well as to clarify the complexities of recording various types of euphemisms in lexicographic practice.
Keywords: euphemism, taboo, metaphorization, variations, tropes, metaphor, metonymy, transference, personification, comparison, synecdoche, lexicography.